Woman in The Dunes by Abe Kobo and Veronika Decides to Die by Paulo Coelho: A Current Study of Existentialism - Ahmad Iklil Saifulloh; Jenny Yudha Pratama (Universitas Negeri Surabaya, 2018)
Soren Kierkegaards the three phases of Human Existence (aesthetic phase, ethic phase and religious phase) combine with a current study of Existentialism by Gordon E. Bigelow (Existence Precedes Essence, Alienation, Fear and Trembling of Anxiety, Nothingness, and Freedom) are the core ideaof this research. The researcher compares the Brazilian novelist Paulo Coelhos novel Veronika Decides to Die and Japanese novelist Abe Kobos novel Woman in the Dunes. This research reveals how the main characters Veronika and Niki are entrapped by society and nature with the sense of nothingness till their enlightenment. By means of using Descriptive Qualitative research, this researchfound the way of the main characters provide the meaning of their life based on the three phases of Existentialism and the Six Prime of Existentialism. Keywords: Existentialism, Six Primes of Existentialism, Three Phases of Human Existence